What Does It Mean To Be Private? Relation Between Teenager Self-Presentation And Their Digital Privacy - Moh. Rifaldi Akbar; Syahrul Hidayanto (Ikatan Sarjana Komunikasi Indonesia, 2023)
This study aims to determine the relationship between privacy management on Instagram and the self-presentation of teenaget. The study took respondents (N=54) who had a Generation Z cohort category. Respondents in this study were students of class VII, VIII, IX at Al Azhar Islamic middle School Kemang Pratama 9 Bekasi City, West Java (SMP Islam Al Azhar Kemang Pratama 9 Kota Bekasi, Jawa Barat). This study uses a positivist paradigm with a quantitative approach. This research design is correlational, which aims to determine the relationship between variables. The independent and dependent variables will be measured simultaneously through a cross-sectional approach. The questionnaire was chosen as a tool to collect data. The questionnaire was created using Google Forms and distributed through the WhatsApp application. The nature of the question is closed, where the respondent can only choose the answer according to the options provided in the questionnaire. The sampling technique used is purposive sampling, with the criteria of respondents being middle school students aged 12-14 years, having an Instagram account, and actively using Instagram for 1-3 years. The results of this study indicate that there is a strong relationship between privacy management on Instagram social media and middle school students' self-presentation. Then, the form of the relationship between the two variables is positive, meaning that the higher the privacy management of middle school students on Instagram, the higher the self-presentation.